The Nguyen Dynasty with the Aesthetic Value of Bronze Relics in Hue - Phan Le Chung; Nguyen Thi Hien Le; Dinh Tran Ngoc Huy (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
This paper aims to analyze the nguyen dynasty with the aesthetic value of bronze relics in hue. The method using observations, experience, synthesis analysis, historical and dialectical methods and draws some educational lessons for students. This study shows that Copper material is also one of the materials used a lot in objects with religious elements such as bronze bells, bronze bells, etc. Last but not elast, the aesthetic value of decorative art on bronze in Hue is also the combination of basic elements and the fusion of cultural factors.